Cytokine and Chemokine Profiling in Cats With Sepsis and Septic Shock - Troia, Roberta; Mascalzoni, Giulia; Agnoli, Chiara; Lalonde-Paul, Denise; Giunti, Massimo; Goggs, Robert (Frontiers in Veterinary Science, 2020)
Background: Sepsis is a life-threatening condition associated with an exacerbated production of both pro- and anti-inflammatory cytokines that can promote a hyperactive response to infection or induce immunoparalysis. Data regarding the immune response to sepsis in cats are scarce. Establishing the profiles of cytokines and chemokines in feline sepsis to characterize the nature of the immune responses to sepsis might enable individualized treatments to be developed and targeted. Objective: To evaluate the cytokine and chemokine network in cats with sepsis and septic shock, and to investigate the associations of these analytes with disease severity and outcome. Methods: Blood samples prospectively collected at presentation of cats with sepsis and septic shock to two veterinary teaching hospitals were analyzed. Forty healthy cats were included as controls. A 19-plex feline cytokine/chemokine magnetic bead assay system was used to measure analytes in citrated plasma samples. Cytokine concentrations were compared between groups using the Kruskal-Wallis test with Dunn’s post-hoc correction for multiple comparisons. Cytokine concentrations were compared between survivors and non-survivors with the Mann-Whitney U test. Odds ratios were calculated using logistic regression. A multivariable logistic regression model for prediction of septic shock was constructed. Results: The study enrolled 35 septic cats. Many cytokines were undetectable in both sick and healthy control cats and were excluded from subsequent analyses. Comparisons of cytokine concentrations among healthy controls, cats with sepsis (n=12) and cats with septic shock (n=23) revealed that sick cats (sepsis or septic shock) had significantly higher plasma concentrations of IL-6, IL-8, KC-like and RANTES compared to healthy controls. The combination of MCP-1, Flt-3L and IL-12 were predictive of septic shock. None of the cytokines analyzed was predictive of outcome in this study population. Conclusion: Plasma concentrations of IL-6, IL-8, KC-like and RANTES are increased in cats with sepsis and may play important roles in pathogenesis. Multivariable modeling suggested that analysis of cytokines might aid differentiation of septic shock from sepsis. None of the cytokines analyzed was predictive of outcome. Measurement of these cytokines might enable future studies to better diagnose and characterize feline sepsis and septic shock.